Development of Indonesia Scientific Publications of Physical Education in Reputable International Journals: A Bibliometric Analysis - Hanief, Yulingga Nanda; Kardiyanto, Deddy Whinata; Winarno, Mashuri Eko; Haqiyah, Aridhotul (Universitas Pendidikan Indonesia, 2021)
This study aimed to determine trends in scientific publications and map the scope of thematic research in the field of Physical Education, especially for articles published in reputable international journals (Scopus) writen by Indonesian authors. The research process was focused on the following questions: (1) how is the productivity of Physical Education publications developing in Indonesia?; (2) who are the main contributors (author, University, and name of publication) for the published publications?; (3) what are the thematic areas that attract the most attention of academics?; and (4) what topics are emerging in the field of publication?. It’s used the Scopus database as the source of bibliometric analysis data for the research sampling process. The samples were 55 articles found through keyword